Legitimacy in Mining Companies: The Effect of Asset Newness and Capital Expenditure on ESG Disclosure - Wiwit Hartanis; Ika Atma Kurniawanti (Universitas KH. Abdul Chalim Mojokerto, 2026)
Amid global sustainability pressures, mining companies are facing intense public scrutiny. Using an integrated framework of Legitimacy, Signaling, and Stakeholder theories, this study examines the influence of physical asset characteristics, specifically asset newness and capital expenditure (CAPEX), on Environmental, Social, and Governance (ESG) disclosure. Using a quantitative design, this study analyzes a purposive sample of 57 observations from mining companies for the period 2020-2024. Data are processed using fixed-effect panel data regression with robust standard errors. ESG disclosure is measured through content analysis based on the OJK index no. 51/POJK/03./2017. The results show that asset newness has a significant negative effect on ESG disclosure, confirming the phenomenon of